Health Education of Honey Consumption in Increasing Hemoglobin Levels of Pregnant Women in Trimester III in Tambusa Barat Village - Andriana Andriana; Ratna Laila (International Journal on Advanced Science, Education, and Religion, 2021)
During the third trimester of pregnancy, pregnant women are expected to have a good enough hb level to prevent anemia and prepare for birth which aims to prevent postpartum hemorrhage, fetal death, maternal death and low birth weight. Based on the results of data in West Tambusai Village in 2022, there were 36 third trimester pregnant women. The purpose of this study was to find out how the understanding of third trimester pregnant women about anemia prevention with honey consumption in Tambusai Barat Village. The methodology of this research uses descriptive analytic. The population in this study amounted to 36 pregnant women in the third trimester and the sample in the study was 30 pregnant women in the third trimester. Sample selection technique using purposive sampling. The results of research on education in third trimester pregnant women in Tambusai Barat Village, in the elementary school group as many as 0 people (0%), junior high school as many as 9 people (30.0%), high school as many as 16 people (53.4%), PT as many as 5 people (16.6%). BMI of pregnant women in the third trimester In Tambusai Barat Village, there is no thin group (0%), ideal body weight is 12 people (40.0%), overweight is 10 people (33.3%), overweight is about 8 people (26.7%). From the research data shows that the knowledge of third trimester pregnant women before being given health education about the benefits of honey has an average of 10.12 and after being given health education has knowledge about the benefits of honey in increasing Hb which is 13.80. It is known that the results of the statistical test of health education have a significant effect on mother's knowledge with p value < 0.05. The conclusions and suggestions that can be given are that the administration of honey is effective in increasing the hemoglobin levels of pregnant women in the third trimester, so after this research it is hoped that the third trimester pregnant women can suggest and implement it to increase hemoglobin levels while preventing anemia in third trimester pregnant women. Keywords: Haemoglobin, Third Trimester Pregnant Women, Health Education, Honey, West Tambusai Village